Emotive AI and the Soul of Heritage: Investigating How Emotionally-Intelligent AI Shapes Cultural Tourism Experiences in Taiwan - Rifqi, Husni Muhamad; Bastiar, Agus (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2024)
As emotionally-intelligent artificial intelligence (AI) becomes increasingly integrated into tourism experiences, its role in shaping cultural engagement warrants deeper exploration. This study investigates how AI emotional recognition and AI-driven cultural storytelling influence tourists’ emotional engagement, perceived cultural authenticity, and overall satisfaction in Taiwan’s heritage tourism context. Drawing on affective computing theory and narrative transportation, the research employs a cross-sectional survey of 235 tourists across three AI-enhanced cultural sites. Using partial least squares structural equation modeling (PLS-SEM), the findings reveal that both AI features significantly enhance emotional engagement, which in turn mediates their effects on authenticity and satisfaction. Perceived authenticity emerges as the strongest predictor of tourist satisfaction, especially in Indigenous heritage sites. Furthermore, tourists with higher cultural interest experience stronger authenticity outcomes from emotionally engaging encounters. These results underscore AI’s potential not only as a functional tool but as an affective co-creator of meaning in cultural tourism. The study contributes to tourism theory by integrating emotional responsiveness into smart tourism discourse and offers practical guidance for AI system design in heritage interpretation.